PRODUCTION OF BETHA-PHENYLTHIO-GAMMA-BUTYROLACTONES - SHIRAI KOZO; WATANABE MIKIO; KUMAMOTO TAKANOBU (1996)
PURPOSE: To obtain the subject compounds which are synthetic intermediates for phenylthio-buten-olides that are physiologically active compounds useful as antimicrobial agents, germicicdes and insecticides in high yield according to a simple reactional process using an inexpensive raw material. CONSTITUTION: (A) A 2-buten-4-olide of formula I is reacted with (B) thiols of the formula HS-R (R is phenyl which may optionally be substituted with a substituent group selected from halogens and lower alkyls) (e.g. thiophenol) in the presence of (C) an organic base (e.g. triethylamine or trihexylamine) to afford β-phenylthio-γ-butyrolactones of formula II. The reaction is preferably carried out by using about 1-2mol component (B) based on the component (A) and about 1-1.2mol component (C) based on the component (A) under conditions of 10-30 deg.C. Furthermore, the resultant compound of formula II is oxidized and the Pummerer rearrangement reaction of the resultant oxidation product is then carried out to afford 3-phenylthio-2-buten-4-olides of formula III.